(untitled) (World Bulletin of Public Health, 2024)
In clinical practice, along with diseases of the cardiovascular system, a quite urgent and social problem is the pathology of the pulmonary system in the form of pneumonia. Pneumonia is a group of acute infectious (mainly bacterial) diseases, different in etiology, pathogenesis, and morphological characteristics, characterized by focal damage to the respiratory parts of the lungs with the obligatory presence of intra-alveolar exudation; the most widespread in humans is community-acquired pneumonia. According to WHO, it ranks 4th on the list of deaths from infectious diseases. In Uzbekistan, the incidence of community-acquired pneumonia is 5-8 people per 1000 people per year among people over 18 years of age. This disease occurs in the community or later than four weeks after discharge, and is diagnosed within 48 hours of hospitalization. At the same time, in elderly people, the incidence of community-acquired pneumonia is 2 times higher than in young people, and the mortality rate among patients over 60 years of age is 10 times higher. One of the factors in the development of severe forms of community-acquired pneumonia in the elderly is the addition of endogenous intoxication.